2011
DOI: 10.1186/1472-6882-11-69
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the antioxidant properties of flowers and roots of Pyrostegia venusta (Ker Gawl) Miers

Abstract: BackgroundFree radical stress leads to tissue injury and can eventually to arthritis, atherosclerosis, diabetes mellitus, neurodegenerative diseases and carcinogenesis. Several studies are ongoing worldwide to find natural antioxidants of plant origin. We assessed the in-vitro antioxidant activities and screened the phytochemical constituents of methanolic extracts of Pyrostegia venusta (Ker Gawl) Miers.MethodsWe evaluated the antioxidant potential and phytochemical constituents of P. venusta using 1,1-Dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 25 publications
5
38
0
1
Order By: Relevance
“…Miers, family Bignoniaceae, is traditionally used to treat erysipelas as well as pulmonary and vaginal infections [9,10]. Compounds isolated from the extracts of this species present antioxidant and antimicrobial activities and elicit hyperpigmentation [11,12]. Veloso et al [13] have reported that this species is useful to treat flu and cold symptoms induced by lipopolysaccharides.…”
Section: Introductionmentioning
confidence: 98%
“…Miers, family Bignoniaceae, is traditionally used to treat erysipelas as well as pulmonary and vaginal infections [9,10]. Compounds isolated from the extracts of this species present antioxidant and antimicrobial activities and elicit hyperpigmentation [11,12]. Veloso et al [13] have reported that this species is useful to treat flu and cold symptoms induced by lipopolysaccharides.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have suggested that inflammatory tissue damage may be due to the liberation of reactive oxygen species from the phagocytes that invade inflammation sites (29,30). DPPH and ABTS radical scavenging assays, based on electron transfer and hydrogen atom transfer reaction, are analytical methods for the reliable determination of antioxidant activities of biological samples in vitro (31). In this study, samples from the EAEG treatment groups exhibited significant DPPH and ABTS radical scavenging activities and these results suggested that free radicals scavenging activities contribute to the antioxidant effects of EAEG in vitro, which may be responsible for its anti-inflammatory activities (32).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant potential of extract was estimated by determining its DPPH radical scavenging capability by adopting the method of Roy et al [15] with minor modifications. The dried methanol extract was diluted from 0.02 mg/ml to 0.12 mg/ ml.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%